2022
DOI: 10.1007/s40618-022-01945-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of erectile dysfunction in COVID-19 patients: a systematic review and meta-analysis

Abstract: Purpose Studies have found that erectile dysfunction (ED) may be a short-term or long-term complication in coronavirus disease 2019 (COVID-19) patients, but no relevant studies have completed a pooled analysis of this claim. The purpose of the review was to comprehensively search the relevant literature, summarize the prevalence of ED in COVID-19 patients, assess risk factors for its development, and explore the effect of the COVID-19 infection on erectile function. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…SARS-CoV-2 viral infections not only causes respiratory damage, but may also have serious effects on the male patients' reproductive system which regulate many physiological processes. Even though it appears that erectile function deteriorates after COVID-19 infection, the function tends to improve over time 18 Patients with COVID-19 have a high risk and prevalence of ED, which may be driven primarily by anxiety, and attention should be paid to patients' erectile function when treating COVID-19 19 . Some researchers have also characterized the histopathology of tissue from patients who recovered from symptomatic COVID-19 infection, nding that the COVID-19 virus is present in the penis long after the initial infection in human 20 .…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 viral infections not only causes respiratory damage, but may also have serious effects on the male patients' reproductive system which regulate many physiological processes. Even though it appears that erectile function deteriorates after COVID-19 infection, the function tends to improve over time 18 Patients with COVID-19 have a high risk and prevalence of ED, which may be driven primarily by anxiety, and attention should be paid to patients' erectile function when treating COVID-19 19 . Some researchers have also characterized the histopathology of tissue from patients who recovered from symptomatic COVID-19 infection, nding that the COVID-19 virus is present in the penis long after the initial infection in human 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have also characterized the histopathology of tissue from patients who recovered from symptomatic COVID-19 infection, finding that the COVID-19 virus is present in the penis long after the initial infection in human [28]. Interestingly, an article suggested that PDE5 inhibitors, therapeutic agents for erectile function, may target potential targets of COVID-19 due to their anti-inflammatory, antioxidant, immune response modulating and anti-apoptotic properties[29] Meanwhile, a cross-sectional study showed that COVID-19 vaccination did not affect male sexual function, including erectile function [30]. In addition to biological and mental health factors, one study demonstrated that COVID-19 may also have a unique detrimental effect on men's health and erectile function through health care access mechanisms [31].…”
Section: Discussionmentioning
confidence: 99%
“…Its occurrence increases drastically from about 6 % in the age group 20–29 years to 50–70 % in the age group 40–79 years. Its rate is projected to increase significantly to over 320 million by 2025 [ [3] , [4] , [5] ]. India is the feebleness capital of the world because of the high infection rate in the male reproductive system and more males [ [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%